Pengaruh Terapi Kelompok terhadap Peningkatan Kualitas Hidup Penderita Kusta: Literature Review - Ernawati Hatuwe; Arlina Dewi (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Leprosy is an infectious disease that causes very complex problems. The quality of life of people affected by leprosy is a matter that needs to be considered, Quality of life (QOL) includes physical health, psychological health, level of independence, social occupancy, personal trust, and relationships with the environment. How to improve the quality of life for lepers. Method: Search from 3 databases namely Pubmed, ProQuest and Google Cindekia using keywords of quality of life or Qol or hqrl and leprosy or morbus hansen or leprae or leprosy and self help groups or mutual-help groups or support group or therapy group or self concept This review identified 10 articles that fit the inclusion criteria. Most articles use quantitative, namely cross-sectional design, 6 articles and 1 article using quasi-experiment, 2 qualitative articles and 1 review literature article. Of the 10 articles selected, 4 articles focused on the quality of life for people affected by leprosy and 6 articles that discussed improving the quality of life for people affected by leprosy. Group therapy can improve the quality of life of people affected by leprosy and make leprosy sufferers have a deeper confidence in facing the community or the environment around